Politeness Interaction Strategy used by Teacher and Students in Lean On Me Movie - Thomas Pandonge (Sintuwu Maroso Journal of English Teaching, 2018)
The objectives of this research are to find out politeness strategies used by Joe Louis Clark and the students in the Lean on Me movie and to find out the dominant types of politeness strategy used by Joe Louis Clark in the movie. This research uses descriptive qualitative approach. The data were in the form of utterances which contains politeness strategies. The data source is Lean on Me movie script. The data are collected by note-taking technique which were later classified and analyzed under the theories of Brown and Levinson (1987). The result of this research shows that there are four types of politeness strategies used by the main characters in Lean on Me movie when having conversation with the students and teacher. The politeness strategies were Bald-on record strategy, Positive politeness strategy, Negative politeness strategy, and Off record strategy. Positive politeness strategy has the highest frequency among other strategies since the dialogues are among teacher and students.Keywords: politeness interaction, interaction among teacher and students,positive politeness strategy